Pengaruh Religiusitas, Norma Subjektif, Perceived Behavioral Control, Dan Kualitas Produk Terhadap Minat Beli Konsumen Produk Kosmetik Bersertifikat Halal - Romizah, Romizah; Mas'ud, Fuad (Diponegoro Journal of Islamic Economics and Business, 2021)
In the 21st century, cosmetics have become one of the most important goods for society, especially for woman in a productive age. The halal certified cosmetics industry in Indonesia is also increasing every year because of highly demand from Indonesian Muslims people. As a muslim, it is a obligation to consume halal cosmetics. This study aims to analyze the effect of religiosity, subjective norms, perceived behavioral control, and product quality on purchase intentions in halal certified cosmetic products. The data collection method was done through a questionnaire. The population this study is muslim female students resided in Semarang who have purchased halal certified cosmetic products in the last 2 months. Sample gathred in this study is  106 respondents. This study uses multiple linear regression analysis techniques using the SPSS 25 application. Results of this study shows that religiosity has no effect on consumer purchase intention on halal certified cosmetic products. Subjective norms, perceived behavioral control, and product quality has effect positively on consumer purchase intention on halal certified cosmetic products.